Damping and Fluidelastic Instability in Two-Phase Cross-Flow Heat Exchanger Tube Arrays - Moran, Joaquin E. (My University, 2007)
An experimental study was conducted to investigate damping and fluidelastic instability in tube arrays subjected to two-phase cross-flow. The purpose of this research was to improve our understanding of these phenomena and how they are affected by void fraction and flow regime. The model tube bundle had 10 cantilevered tubes in a parallel-triangular configuration, with a pitch ratio of l.49. The two-phase flow loop used in this research utilized Refrigerant 11 as the working fluid, which better models steam-water than air-water mixtures in terms of vapour-liquid mass ratio as well as permitting phase changes due to pressure fluctuations. The void fraction was measured using a gamma densitometer, introducing an improvement over the Homogeneous Equilibrium Model (HEM) in terms of void fraction, density and velocity predictions. Three different damping measurement methodologies were implemented and compared in order to obtain a more reliable damping estimate. The methods were the traditionally used half-power bandwidth, the logarithmic decrement and an exponential fitting to the tube decay response. The decay trace was obtained by "plucking" the monitored tube from outside the test section using a novel technique, in which a pair of electromagnets changed their polarity at the natural frequency of the tube to produce resonance. The experiments showed that the half-power bandwidth produces higher damping values than the other two methods. The primary difference between the methods is cam,ed by tube frequency shifting, triggered by fluctuations in the added mass and coupling between the tubes, which depend on void fraction and flow regime. The exponential fitting proved to be the more consistent and reliable approach to estimating damping. In order to examine the relationship between the damping ratio and mass flux, the former was plotted as a function of void fraction and pitch mass flux in an iso-contour plot. The results showed that damping is not independent of mass flux, and its dependency is a function of void fraction. A dimen~; ional analysis was carried out to investigate the relationship between damping and two-phase flow related parameters. As a result, the inclusion of surface tension in the form of the Capillary number appears to be useful when combined with the twophase component of the damping ratio (interfacial damping). A strong dependence of damping on flow regime was observed when plotting the interfacial damping versus the void fraction, introducing an improvement over the previous result obtained by normalizing the two-phase damping, which does not exhibit this behaviour. The interfacial velocity model was selected to represent the fluidelastic data in two-phase experiments, due to the inclusion of the tube array geometry and density ratio effects, which does not exist for the pitch velocity approach. An essential component in reliably establishing the velocity threshold for fluidelastic instability, is a measure of the energy dissipation available in the system to balance the energy input from the flow. The present analysis argues that the damping in-flmv is not an appropriate measure and demonstrates that the use of quiescent fluid damping provides a better measure of the energy dissipation, which produces a much more logical trend in the stability behaviour. This value of damping, combined with the RAD density and the interfacial velocity, collapses the available data well and provides the expected trend of two-phase flow stability data over the void fraction range from liquid to gas flows. The resulting stability maps represent a significant improvement over existing maps for predicting fluiclelastic instability of tube bundles in two-phase flows. This result a1so tends to confirm the hypothesis that the basic mechanism of fluidelastic instability is the same for single and two-phase flows.
Keywords: Fluidelastic instability; two phase cross flow; heat exchanger; Engineering; Philosophy; Physical Sciences and Mathematics; Engineering